Adopting complementary and integrative medicine: Effects of Antox® and Bactofort® administrations on clinico-pathological changes in pullets inoculated with a very virulent infectious bursal disease virus - Andamin, Aliyu Danlami; Orakpoghenor, Ochuko; Markus, Talatu Patience; Akade, Felix Tertsua; Abdu, Paul Ayuba; Aluwong, Tagang (International Journal of Veterinary Sciences Research, 2023)
This study evaluated the ameliorative effects of Antox® and Bactofort® on clinico-pathological changes in ISA Brown chicks inoculated with a very virulent infectious bursal disease virus (vvIBDV). Two hundred (200) ISA Brown day-old chicks were randomly assigned into four groups (A to D) of 50 birds each. Groups A, and B were administered with Antox®, and Bactofort®, respectively from day-old to 42 days of age, and inoculated with vvIBDV at 28 days of age. Groups C, and D served as positive, and negative controls, respectively. Clinical signs, morbidity and mortality rates, gross and histopathological changes were determined. The clinical signs were moderate in groups A and B, but severe in group C and absent in group D by 7 days post-inoculation (dpi). Morbidity and mortality rates were lower in groups A and B compared to C. Gross and histopathological lesions were less severe in groups A and B compared to C. Antox® and Bactofort® ameliorated the negative effects of vvIBDV. Antox® and Bactofort® could be recommended for use in vvIBDV outbreaks to ameliorate the negative effects due to the infection.